Performance evaluation of hybrid fiber reinforced low strength concrete cylinders confined with CFRP wraps. (June 2021) - Raza, Ali; Rafique, Umer; Masood, Bilal; Ali, Babar; ul Haq, Faraz; Asad Nawaz, Muhammad
Abstract: The improvement in the compressive strength (CS) and ductility of plain concrete always remained an active area for advanced research. The present study aims to enhance the strength of low strength hybrid fiber reinforced concrete (HFRC) cylinders confined with different number of carbon fiber reinforced polymer (CFRP) sheets by examining the axial CS, axial compressive strain, and compressive stress–strain behavior of low strength HFRC cylinders confined with CFRP sheets. The HFRC consisted of steel fibers and polypropylene fibers. Two groups of low strength HFRC specimens (12.5 MPa and 16.5 MPa) were fabricated to investigate the effect of CFRP confinement on the different CS of HFRC. The experimental outcomes depicted that the lateral CFRP confinement of concrete significantly improved the CS, axial compressive strain, and axial stiffness of low strength HFRC specimens. The improvements of 115.7% and 130.7% occurred in the CS of 12.5 MPa group for single and double CFRP layers, respectively. Similarly, the improvements of 37.4% and 112.6% occurred in the CS of 16.5 MPa group for single and double CFRP layers, respectively. Therefore, the CFRP confinement is more effective for low strength HFRC as compared with high strength HFRC in terms of axial CS and axial compressive strain.